AGE AND GENDER DIFFERENCES IN ALCOHOL, TOBACCO, AND SUBSTANCE USE, REPRODUCTIVE HEALTH, AND AWARENESS OF SEXUALLY TRANSMITTED DISEASE PREVENTION AMONG SECONDARY SCHOOL STUDENTS IN BUKITTINGGI, INDONESIA - D. NINDREA , Ricvan; C. MING , Long; HENDRIYANI , Heni (African Journal of Infectious Diseases (AJID), 2025)
Background: The variations in behavioral health issues by sex and age among adolescents in Indonesia have not been comprehensively explored. This study aimed to describe age and gender based differences in alcohol consumption, tobacco and substance use, reproductive health knowledge, and awareness of sexually transmitted disease (STD) prevention among high school students in Bukittinggi, Indonesia. Materials and Methods: This study employed a school-based cross-sectional design conducted in Bukittinggi Municipality, West Sumatra Province, Indonesia, with a sample size of 254 secondary school students. We used multi-stage stratified clustered sampling technique to select the students, and asked the students to complete self-administered questionnaires during class on a regular school day. Data analysis was performed using descriptive statistics, and the Chi-square test. Results: The study revealed that while the majority had never used alcohol, tobacco, electronic cigarettes, and substances, there were still some former drinkers and smokers, as well as current smokers and electronic cigarette users, especially among males aged 14-15 years. A small percentage also reported using analgesics and energy drinks. The participants generally received education about AIDS or HIV at school, but there were some misconceptions and stigmatizing attitudes toward HIV-positive individuals. Health education regarding birth control was not universal. Awareness of safe sex or STD prevention methods varied by age and gender, with varying levels of knowledge about abstinence and condom use. Conclusion: We found slight variations among male and female students. The study findings suggested the need for sex-specific targeted interventions to improve behavioral health issues.